2003
DOI: 10.1080/00288330.2003.9517146
|View full text |Cite
|
Sign up to set email alerts
|

Benthic community dynamics during summer low‐flows in two rivers of contrasting enrichment 1. Periphyton

Abstract: Many foothill rivers in the eastern regions of New Zealand undergo severe reductions in flow during summer. These reductions are often exacerbated by abstractions for out-of-river uses. It has been observed that at such times some river ecosystems are more detrimentally affected by reduced flows than others. We hypothesised that the degree of degradation in river ecosystems during summer low-flows is dependent on a river's enrichment status. We examined the effect of low flows on periphyton community dynamics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 32 publications
0
45
0
Order By: Relevance
“…This river has a high conductivity suggesting higher levels of enrichment. Extensive blooms of filamentous algae were recorded in the companion study (Suren et al 2003). Gauging stations have operated in both rivers for over 10 years, and examination of the historical hydrological data showed that discharge during the study was the second lowest on record.…”
Section: Study Sites and Field Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This river has a high conductivity suggesting higher levels of enrichment. Extensive blooms of filamentous algae were recorded in the companion study (Suren et al 2003). Gauging stations have operated in both rivers for over 10 years, and examination of the historical hydrological data showed that discharge during the study was the second lowest on record.…”
Section: Study Sites and Field Methodsmentioning
confidence: 99%
“…These sites are described in Suren et al (2003), so only a brief account is given here. The Okuku River flows through a catchment dominated by unmodified land cover with a geology dominated by nutrient-poor metamorphic greywacke rocks.…”
Section: Study Sites and Field Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such responses have been widely documented to inform management decisions about the implementation of environmental flows; i.e., the flows left in streams to sustain biodiversity, ecological integrity and ecosystems service (Acreman & Dunbar, 2004;Brisbane Declaration, 2007;Arthington et al, 2010). Nonetheless studies on the relationships between flow reduction and responses of stream algal assemblages are scarce compared with those dealing with macroinvertebrates and fishes, and most such studies are focused mainly on single streams in temperate or subtropical latitudes (Clausen & Biggs, 1997;Downes et al, 2003;Soininen, 2003;Suren et al, 2003;Wang et al, 2009;Wu et al, 2009). Comparable studies on tropical or monsoonal streams-with markedly seasonal flow regimes-are scarce (Niu & Dudgeon, 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…Physical shear stress imposed by current strongly influences the relative abundance of algae with different growth forms or morphologies (e.g., erect, prostrate, or filamentous) and also affects colonization dynamics, thereby influencing species composition (Stevenson, 1996;Hart & Finelli, 1999). With reduced current speed and flow volume, algal community development is less constrained by shear stress, and compositional shifts can take place from, for instance, low-stature diatoms to nuisance growths of filamentous green algae, although the precise outcome depends on nutrients and temperature regimes (Biggs & Price, 1987;Suren et al, 2003;Berthon et al, 2011). The strength of grazing pressure upon epibenthic algae can vary according to flow conditions (Poff & Ward, 1995;Chester & Norris, 2006), potentially influencing the intensity of topdown control of assemblage composition and biomass (Opsahl et al, 2003).…”
Section: Introductionmentioning
confidence: 99%